Preclinical evaluation of AFM24, a novel CD16A-specific innate immune cell engager targeting EGFR-positive tumors. Issue 1 (1st January 2021) - Wingert, Susanne; Reusch, Uwe; Knackmuss, Stefan; Kluge, Michael; Damrat, Michael; Pahl, Jens; Schniegler-Mattox, Ute; Mueller, Thomas; Fucek, Ivica; Ellwanger, Kristina; Tesar, Michael; Haneke, Torsten; et al.
ABSTRACT: Epidermal growth factor receptor (EGFR)-targeted cancer therapy such as anti-EGFR monoclonal antibodies and tyrosine kinase inhibitors have demonstrated clinical efficacy. However, there remains a medical need addressing limitations of these therapies, which include a narrow therapeutic window mainly due to skin and organ toxicity, and primary and secondary resistance mechanisms of the EGFR-signaling cascade (e.g., RAS-mutated colorectal cancer). Using the redirected optimized cell killing (ROCK®) antibody platform, we have developed AFM24, a novel bispecific, IgG1 -scFv fusion antibody targeting CD16A on innate immune cells, and EGFR on tumor cells. We herein demonstrate binding of AFM24 to CD16A on natural killer (NK) cells and macrophages with KD values in the low nanomolar range and to various EGFR-expressing tumor cells. AFM24 was highly potent and effective for antibody-dependent cell-mediated cytotoxicity via NK cells, and also mediated antibody-dependent cellular phagocytosis via macrophages in vitro . Importantly, AFM24 was effective toward a variety of EGFR-expressing tumor cells, regardless of EGFR expression level and KRAS/BRAF mutational status. In vivo, AFM24 was well tolerated up to the highest dose (75 mg/kg) when administered to cynomolgus monkeys once weekly for 28 days. Notably, skin and other toxicities were not observed. A transient elevation of interleukin-6 levels was detected at all dose levels, 2–4 hours post-dose, which returned to baseline levels after 24 hours. These results emphasize the promise of bispecific innate cell engagers as an alternative cancer therapy and demonstrate the potential for AFM24 to effectively target tumors expressing varying levels of EGFR, regardless of their mutational status. Abbreviations: ADA: antidrug antibody; ADCC: antibody-dependent cell-mediated cytotoxicity; ADCP: antibody-dependent cellular phagocytosis; AUC: area under the curve; CAR: chimeric-antigen receptor; CD: Cluster of differentiation; CRC :colorectal cancer; ECD: extracellular domain; EGF: epidermal growth factorEGFR epidermal growth factor receptor; ELISA: enzyme-linked immunosorbent assay; FACS: fluorescence-activated cell sorting; Fc: fragment, crystallizableFv variable fragment; HNSCC: head and neck squamous carcinomaIL interleukinm; Ab monoclonal antibody; MOA: mechanism of action; NK :natural killer; NSCLC: non-small cell lung cancer; PBMC: peripheral blood mononuclear cell; PBS: phosphate-buffered saline; PD: pharmacodynamic; ROCK: redirected optimized cell killing; RSV: respiratory syncytial virus; SABC: specific antibody binding capacity; SD: standard deviation; TAM: tumor-associated macrophage; TKI: tyrosine kinase inhibitor; WT: wildtype